The impact of empowering leadership style and leader-member exchange on performance appraisal reactions - Liang Kaijing (2019)
Existing studies about the performance appraisal reactions in the academic field have discussed several factors affecting the quality of it and its role in an organization. The purpose of this study focuses on contributing the relationship between empowering leadership style and performance appraisal reactions. The LMX is a mediator within this relationship. The empowering leadership level of supervisors were evaluated with a 5-dimension scale and performance appraisal reactions of subordinates were evaluated with a 3-dimension scale by employees. In addition, this study also examined the mediation effect of a variable between empowering leadership style and performance appraisal reactions which is LMX with a 7-item scale. The result came from a great amount of samples which were collected from 219 employees in southern China. The result of the present study indicated that empowering leadership style is positively related to performance appraisal reactions directly and this relationship is also positively and significantly mediated by LMX quality. Therefore, this study suggested that organizations can increase the quality of performance appraisal reactions with altering the leadership style of supervisors and increasing the LMX quality. The limitation and future study are presented and followed by the conclusion part.